Kinetic investigations of formation of polyimides containing arylene sulfone ether linkages by potentiometric titration and their characterization - Yilmaz, T; Guclu, H; Ozarslan, O; Yildiz, E; Kuyulu, A; Ekinci, E; Gungor, A (JOHN WILEY & SONS INC, 1997)
In this work, thermal solution imidization kinetics of two high performance polyimides, prepared from the polycondensation of pyromellitic dianhydride (PMDA) and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) with 4,4'-bis(3-aminophenoxy)diphenylsulfone (DAPDS) were investigated using nonaqueous titration technique with tetramethylammonium hydroxide. Most of the kinetic investigations, found in the literature, are based on the aromatic p-diamines.(1,2) In the present work, attention was focused on imidization kinetics with m-substituted aromatic diamines having electron donating (-O-) and electron withdrawing (-SO2-) groups in the same molecule. Kinetic parameters, namely the rate constants, activation energies, ies, entropies and enthalpies of imidization reactions were determined and compared with the literature values. It is reported in literature(3) that electron affinities of dianhydrides and ionization potentials of diamines, have strong influence on the reaction rate and activation energies of imidization. Activation energy (E-a) values were found to be 66 and 57 kJ/mol for DAPDS/PMDA and DAPDS/BTDA respectively, and order of reaction was found to be second order. Polyimides DAPDS/PMDA. and DAPDS/BTDA, subjected to kinetic investigation, showed glass transition temperatures of 267 degrees C and 241 degrees C, both were found to be thermally stable up to 500 degrees C. (C) 1997 John Wiley & Sons, Inc.
Keywords: solution imidization; kinetics; IMIDIZATION; Polymer Science